EFFECT OF BRAND CREDIBILITY TO WORD OF MOUTH VIA CUSTOMER SATISFACTION AND CUSTOMER LOYALTY AT HYPERMART CYBERPARK KARAWACI - Kusuma, Alvin; Wuisan, Dewi Sri Surya (Universitas Negeri Yogyakarta, 2021)
Retail business development becomes very competitive due to offline and online competitor. Business owner has to offer the best services for costumers because customers' dynamic behavior may let them to try other brands if their needs was not fulfilled. As the numbers of competitors keep increasing and company must have good positioning and credibility to maintain their customers and give positive Word of Mouth. The purpose of this study was to find out the effect of Brand Credibility to Word of Mouth via Customer Satisfaction and Customer Loyalty as intervening variable at Hypermart Cyberpark Karawaci. The sampling technique used in this study was a non-probability purposive sampling. While the analysis technique was using Partial Least Square (PLS) - Structural Equation Modeling (SEM). Respondents were taken from 230 customers of Hypermart Cyberpark Karawaci in Tangerang with particular characteristics. The results showed that Customer Satisfaction and Customer Loyalty were intervening variable between Brand Credibility on Word of Mouth, there was influence of Brand Credibility on Customer Satisfaction and Customer Loyalty, there is influence of Customer Satisfaction and Customer Loyalty on Word of Mouth, and there is influence of Customer Satisfaction on Customer Loyalty.